MORPHOLOGICAL CHANGES IN ORGANS AND TISSUES AT SUBCHRONIC INTOXICATION WITH BENZODIAZEPINE MEDICATIONS (EXPERIMENTAL RESEARCHES) - V. V. Zakharenkov; L. G. Gorokhova; O. I. Bondarev; M. S. Bugaeva (Acta Biomedica Scientifica)
Morphological changes in tissues and organs at subchronic intoxication of white rats with 1,4-benzodiazepines synthetic medications (alprazolame, mezapame, diazepame, and nozepame) are studied in an experiment. Pathomorphological changes in tissues of liver, kidneys, brain and reproductive system that can lead to the development of industrially caused diseases in the employees of benzodiazepines production are revealed.